TỔNG HỢP VÀ ĐẶC TRƯNG VẬT LIỆU SBA-15 CHỨC NĂNG HÓA NHÓM THIOL: ẢNH HƯỞNG CỦA HÀM LƯỢNG NGUỒN CUNG CẤP NHÓM THIOL - Thu Phương, Trần Thị; Viễn, Võ (Vietnam Journal of Chemistry, 2012)
Thiol-functionalized mesoporous silicas have been synthesized by co-condensation of 3-mercaptopropyl-trimethoxysilane (MPTMS) and tetraethoxysilane (TEOS) in acidic medium with the block copolymer Pluronic 123 as a structure directing agent. The influence of the molar ratio MPTMS/(TEOS+MPTMS) on the textural properties has been investigated. The products were characterized by low-angle XRD, nitrogen adsorption–desorption, TGA, transmission electron microscopy, and elemental chemical analysis. The results show that the amount of thiol incorporated to the materials is in accordance with the MPTMS/(TEOS+MPTMS) proportion in the reaction mixture but increasing incorporated thiol leads to a reduction of the textural and structural properties of materials.